AN ERROR ANALYSIS ON BROADCASTING STUDENTS’ MID-TERM TEST OF AKRB YOGYAKARTA - Marita Nurharjanti; Rosyidah Jayanti Vijaya; Agus Wibowo; Efrat Tegris (Bajang Institute, 2024)
This paper aims at analyzing errors made by the fourth semester students of Radya Binatama Communication Academy Yogyakarta. Analyzing students’ errors is necessary so that teachers can plan their suitable methods for the students hoping that the errors can be minimized significantly. The data were taken from 33 students attending English 1 Mid-Term Test of the Academic Year 2022/2023. One of the instructions in the test was to write about their unforgettable experience (recount text). This research used descriptive qualitative method. The data analysis technique used four steps: identifying, classifying, describing, and calculating. The errors were classified into two sources of error: interlingual and intralingual errors. Then, the errors were described into four types: misordering, addition, omission and misformation. The result showed from the total 178 errors, the most frequent source of errors was intralingual error: 139 errors (78,09%), interlingual error: 39 (21,91%). Based on the types of errors, misordering occurred 14 times (7,87%), addition 25 times (14,04%), omission 45 times (25,29%) and misformation 94 times (52,80%). These facts can be essentially used by the teacher to focus on what should be revised to improve the quality of teaching and learning significantly.